Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays L. Saccharata Sturt.) Akibat Defoliasi Daun Pada Waktu dan Jumlah Yang Berbeda-Beda - Ngawit, I Ketut; Santoso , Bambang Budi (LPPM Universitas Mataram, 2024)
One effort to increase sweet corn production is to defoliate the leaves at the right time. The problem is, how many leaves and when is the right time to defoliate them is not yet known. Therefore, research was conducted which aimed to determine the effect of the number of leaves and defoliation time interval on the growth and yield of sweet corn. The research was carried out in Nyurlembang Village, Narmada District, West Lombok Regency, in July - November 2022. Experimental research method with a factorial completely randomized block design grouped into three blocks. The first factor tested was the number of leaves defoliated, namely 0, 2, 4 and 6 pieces. The second factor is defoliation time, namely when the plants are 28, 42 and 56 days after planting.. Data were analyzed using farian analysis and continued with the LSD test at the 5% level. The results showed that defoliation of the number of leaves at different times had a significant effect on the growth and yield of sweet corn. There was no interaction between the two independent variables on the growth and yield of sweet corn. Defoliation of 2 leaves carried out when the plants were 28 HST had a negative effect on plant growth and yield and was not significantly different from no defoliation treatment. Defoliation of 4-6 strands carried out when the plants were 42 – 56 HST, was able to produce cob length, cob diameter, number of rows of cobs-1, weight of fresh cobs ha-1, dry shell weight ha-1; and the weight of 100 dry seeds is significantly higher than the defoliation of 2 leaves and 0 leaves, so it needs to be applied in future sweet corn planting efforts.